Early-life adversities are associated with lower expected value signaling in the adult brain: archival report - Sacu, Seda; Dubois, Magda; Hezemans, Frank H.; Aggensteiner, Pascal; Monninger, Maximilian; Brandeis, Daniel; Banaschewski, Tobias; Hauser, Tobias U.; Holz, Nathalie E. (Biological psychiatry, 2024)
Background - Early adverse experiences are assumed to affect fundamental processes of reward learning and decision making. However, computational neuroimaging studies investigating these circuits in the context of adversity are sparse and limited to studies conducted in adolescent samples, leaving the long-term effects unexplored. - Methods - Using data from a longitudinal birth cohort study (n = 156; 87 female), we investigated associations between adversities and computational markers of reward learning (i.e., expected value, prediction errors). At age 33 years, all participants completed a functional magnetic resonance imaging-based passive avoidance task. Psychopathology measures were collected at the time of functional magnetic resonance imaging investigation and during the COVID-19 pandemic. We applied a principal component analysis to capture common variations across 7 adversity measures. The resulting adversity factors (factor 1: postnatal psychosocial adversities and prenatal maternal smoking; factor 2: prenatal maternal stress and obstetric adversity; factor 3: lower maternal stimulation) were linked with psychopathology and neural responses in the core reward network using multiple regression analysis. - Results - We found that the adversity dimension primarily informed by lower maternal stimulation was linked to lower expected value representation in the right putamen, right nucleus accumbens, and anterior cingulate cortex. Expected value encoding in the right nucleus accumbens further mediated the relationship between this adversity dimension and psychopathology and predicted higher withdrawn symptoms during the COVID-19 pandemic. - Conclusions - Our results suggested that early adverse experiences in caregiver context might have a long-term disruptive effect on reward learning in reward-related brain regions, which can be associated with suboptimal decision making and thereby may increase the vulnerability of developing psychopathology.
Online verfügbar: 16. April 2024, Artikelversion: 11. November 2024
Gesehen am 17.04.2025